(NiSKUSSTAO I \MOCII(B.s (N|TIKA \STETIKAs - (Ns(B.(NrAPPOPORTs ((NmOSKWAs (NmUZYKAs, 1968)
(NkOGDA WSTRE^A@TSQ DWA \STETIKA WOZNIKAET TRI TO^KI ZRENIQ(B- (NW \TOJ [UTKE SOWETSKOGO U^ENOGO ESTX DOLQ ISTINY(B.s
Keywords: (N\STETIKAs